Extreme Bodies in the Fiction of Wilkie Collins - Reilly, Esther (Trinity College Dublin. School of English. Discipline of English, 2024)
This thesis places Wilkie Collins's work in the context of nineteenth-century debates on extreme bodily differences, ranging from physical disability to exceptional ability. Recurrent in Collins's fiction are extreme bodies whose extraordinary, sensational, and unusual physical differences simultaneously fascinated and terrified the Victorian imagination. Collins created multiple characters with extreme physical differences, living with the social consequences of being marginalised in a society that privileged normalcy. However, Collins's sensation fiction parallels its unusual characters and the Victorian freak show performers who transgressed normative physical boundaries, and many of his fictional characters would not look out of place in a typical freak show of the period. As a sensation writer and playwright primarily concerned with the marginalised and unconventional and whose fiction required unusual catalysts for his intriguing and mysterious plots, Collins shows particular interest in extreme bodies but, more importantly, in the meanings attached to their bodily difference. Although much of Collins's fictional work is populated by freakish and disabled characters, including The Woman in White and The Moonstone, some the most physically extreme characters he created are found in novels that have received relatively little critical attention, namely Hide and Seek (1854), No Name (1862), Man and Wife (1870), Poor Miss Finch (1872), and The Law and the Lady (1875), which are examined in individual chapters in this dissertation. These chapters will also discuss minor characters from Collins's other works, highlighting their physical differences and relevance in understanding nineteenth-century debates on disability, race, ethnicity, gender, and social classes.
APPROVED
Keywords: Disability Studies; Wilkie Collins; Extreme Bodies; Victorian Literature and Culture; Victorian Disability; Freak Show; Extraordinary Bodies; Freak Studies